Consumer acceptance and nutritional potential of products made from quinoa, chocho, broad bean and maize flours: An age-segmented study in the hospitality sector - Haro-Sosa, Giovanny; Falconí, Paúl Roberto Pino; Núñez, Telmo Marcelo Zambrano; Hermida, Carlos Eduardo Cevallos (Edelweiss Applied Science and Technology, 2025)
This study examines the nutritional properties and consumer acceptance of food products made from quinoa (Chenopodium quinoa), chocho (Lupinus mutabilis), broad bean (Vicia faba), and maize (Zea mays) flours within the hospitality sector. A total of 80 participants, segmented into four age groups (20–29, 30–39, 40–49, ≥50 years), evaluated prototype cookies to assess flavor, texture, aroma, and overall acceptance. In addition, physicochemical analyses were conducted to determine each flour’s composition (proteins, lipids, fiber, ash, and carbohydrates). The results revealed that chocho and broad bean stood out in terms of protein, while quinoa and maize offered a balanced nutritional profile with competitive acceptability. The younger group showed greater openness to novel ingredients, whereas older participants tended to prefer more familiar flavors. Using a partial least squares structural equation modeling (PLS-SEM) approach, the influence of age on the preference for non-traditional flours was confirmed. These findings underscore the importance of implementing segmented strategies in the hospitality sector, highlighting healthier and culturally relevant alternatives.